Investigate the Properties of Concrete as Partial Replacement of Cement With Egg Shell Powder (International Journal of Innovative Research in Computer Science & Technology, 2023)
Concrete is a highly consumed material  in construction field due to its advantages because of this  the natural resources are depleting day by day at an  alarming rate and there is an immediate need for finding  alternate materials to the natural materials in concrete. So,  in my study M30 grade concrete is adopted and the cement  was replaced with Egg Shell powder with different  percentages of 5%, 10%, 15% and 20% and M-Sand with  a constant percentage of 40%. Concrete was casted, cured  and then Compressive, Split Tensile and Flexural tests  were carried out to find the best combination which results  in optimum percentage of strength. The optimum  percentage egg shell powder (ESP) is obtained at15%. At  optimum ESP the Fine Aggregate is replaced with M-Sand  with a constant percentage of 40%. It is the best solution  for disposing of used egg shell and to solve the scarcity of  sand.
Keywords: Egg Shell Powder; Concrete; Coarse Aggregate; Surface Texture